Game theory and behavior - Carpenter, Jeffrey; Robbett, Andrea (London Mit press, 2022)
This introductory text on game theory provides students with both the theoretical tools to analyze situations through the logic of game theory and the intuition and behavioral insights to apply these tools to real-world situations. It is unique among game theory texts in offering a clear, formal introduction to standard game theory while incorporating evidence from experimental data and introducing recent behavioral models. Students will not only learn about incentives, how to represent situations as games, and what agents (3z(Bshould(3y (Bdo in these situations, but they will also be presented with evidence that either confirms the theoretical assumptions or suggests a way in which the theory might be updated.s
Keywords: Human behavior; Game Theory; Economics psychological aspects